Herméneutique et incarnation du soi : Principes de la génération de sens - Paulo Renato Jesus (Funes)
Between the passibility of the flesh and narrative self-understanding, every human self unfolds itself as a semiotic artwork at once affective and creative. Contrary to an all-powerful and all-encompassing vision of hermeneutics as free self-generation of meaning, this article presents an attempt to identify the field of mediations that produce the intelligible relationship of oneself to oneself within intersubjective movements of meaning. In this way, the contributions of narrative and developmental psychology, phenomenology of memory and hermeneutics of the self are put into dialogue for mapping the symbolic space where a vulnerable living flesh becomes a storied self among selves. The vulnerability of the living flesh is metaphorically called naked skin exposed to traumatic events that require the invention of passages through effective signs, capable of opening new possible bodies and worlds.